In vitro Modulation of Cytochrome P450 Isozymes and Pharmacokinetics of Caffeine by Extracts of Hibiscus sabdariffa Linn Calyx. (2019)
Background: Hibiscus sabdariffa beverage (HSB) is widely consumed as a medicinal herb and sometimes used concomitantly with drugs. This study evaluated the in vitro inhibitory potential of the aqueous extract of H. sabdariffa calyces (AEHS) on selected cytochrome P450 (CYP) isozymes and the effect of HSB on the pharmacokinetics of caffeine in vivo. Methods: In vitro inhibitions of eight major CYP isozymes by AEHS were estimated by monitoring CYP-specific model reactions of 10 CYP probe substrates using N-in-one assay method. Subsequently, an open, randomized, two-period crossover design was used to evaluate the effect of HSB on the pharmacokinetics of single-dose 200 mg caffeine in six healthy human volunteers. Blood samples were obtained at specific times over a 24 h period. Probe drugs and metabolites were analyzed in their respective matrices with ultra-performance liquid chromatography/mass spectrometer/mass spectrometer and reversed-phase high-performance liquid chromatography/ ultraviolet detection. Results: The H. sabdariffa aqueous extract weakly inhibited the selected CYP isozymes in vitro, with IC50 of >100 μgmL-1 in the order of CYP1A2 > CYP2C8 > CYP2B6 » CYP2D6 > CYP2C19 > CYP3A4 > CYP2A6 > CYP2C9. HSB decreased terminal t1/2 and Tmax of caffeine by 13.6% and 13.0%, respectively, and increased Cmax by 10.3%. Point estimates of primary pharmacokinetic endpoints, Cmax = 1.142 (90% confidence interval (CI) = 0.882, 1.480) and AUC0–∞ = 0.992 (90% CI = 0.745, 1.320), were outside the 90% CI of 0.8–1.25 bioequivalence limits. Conclusion: The aqueous extract of H. sabdariffa weakly inhibited eight CYP isozymes in vitro, but HSB modified the exposure to caffeine in human. Caution should be exercised in administering HSB with caffeine or similar substrates of CYP1A2 until more clinical data are available.